A Efficient Approach Used for Identifying Distraction of statue Image (International Journal of Engineering and Computer Science, 2014)
In this study, we mainly concentrate on  measuring the different features of  statues  inorder to maintain it’svolubility.There is a need to maintain valuable status in our  world  from the  possible  disasters. For this purpose, a different part of the image is captured and  its  parametric  values were validated with the pre available  dataset of those  statues.The main objective of this paper is to rebuilt  the originality of the statues in case of any damages. The technique to be used  here is Artificial neural network inorder to estimate its different parameters incase of any damage.